Plasma Polymerization of 3‐Aminopropyltrietoxysilane (APTES) by Open‐Air Atmospheric Arc Plasma Jet for In‐Line Treatments. Issue 10 (23rd August 2016) - Ben Said, Sarab; Arefi‐Khonsari, Farzaneh; Pulpytel, Jerome
Abstract : In this work, an open‐air arc plasma jet has been studied to polymerize 3‐aminopropyelthrietoxysilane (APTES), which is the most commonly used aminosilane to functionalize surfaces with amine groups. Although the discharge produced from air is highly oxidative and the gas temperature is high as compared to other atmospheric plasma sources, amine groups, as well as amide ones, were identified in the nanometers thick coatings by XPS and FTIR analysis. By comparing the results with post‐treatment and ‐grafting experiments, the partial retention of amine groups might be explained by the non‐ideal mixing of the precursor flow with the main gas stream inside the plasma jet. Beside the intrinsic plasma reactivity, hydrodynamics effects are indeed important when considering flowing atmospheric plasmas. Abstract : 3‐Aminopropyltriethoxysilane (APTES) nanocoatings have been deposited by an atmospheric pressure plasma jet produced generated from air and APTES mixtures. The retention of amine groups in the organosiloxane coatings is studied and compared to post‐treated and ‐grafted APTES coatings.